2005
DOI: 10.1515/jpm.2005.092
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcomes and the use of oral hypoglycemic agents

Abstract: We believe that glyburide and acarbose can be promising alternative therapies for the treatment of GDM. Glyburide controlled glucose levels in most patients and it was more efficient than acarbose. Glyburide showed a higher rate of macrosomia and neonatal hypoglycemia as compared to other therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
2
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 17 publications
4
123
2
13
Order By: Relevance
“…Another recent study found higher rates of macrosomia and neonatal hypoglycemia in the neonates whose mothers were treated with glyburide. 58 Further, it appears that approximately 20% of women treated with glyburide will fail this management resulting in less time to optimally achieve control with insulin. 56,59,60 Given the lack of further confirmation on the findings regarding the safety and efficacy of glyburide by large, randomized controlled studies and the limitations of observational studies, the ACOG has designated the use of glyburide in pregnancy to be experimental.…”
Section: Use Of Oral Agents Contraindicatedmentioning
confidence: 99%
“…Another recent study found higher rates of macrosomia and neonatal hypoglycemia in the neonates whose mothers were treated with glyburide. 58 Further, it appears that approximately 20% of women treated with glyburide will fail this management resulting in less time to optimally achieve control with insulin. 56,59,60 Given the lack of further confirmation on the findings regarding the safety and efficacy of glyburide by large, randomized controlled studies and the limitations of observational studies, the ACOG has designated the use of glyburide in pregnancy to be experimental.…”
Section: Use Of Oral Agents Contraindicatedmentioning
confidence: 99%
“…The rate of large for gestational age fetuses in each group was 3.7%, 25% and 10.5% respectively. [15] At term, in our study, there was 9.1% and 13.1% of babies in acarbose group and insulin groups respectively with birth weight >3.5 kg. Hypoglycaemia was not there in any of the babies from acarbose group while 21.3% of babies had hypoglycemia in the insulin group.…”
Section: Discussionmentioning
confidence: 44%
“…Bertini AM et al found that glucose control was not achieved in 42.1% of patients using Acarbose. [15] Spellacy, WN Miller, S Winegar found that Macrosomia was present in 50% of pregnancies with GDM. [16] Langer et al also found 50% of pregnant patients with GDM to have macrosomia.…”
Section: Discussionmentioning
confidence: 99%
“…A glibenclamida é considerada a melhor opção entre as sulfonilureias para utilização em gestantes, sendo considerada segura para emprego a partir do segundo trimestre de gestação (10,29,30).…”
Section: Glibenclamidaunclassified
“…Estudos animais mostraram ausência de teratogenia em doses 32 vezes maiores que a dose terapêutica humana (26). Até o momento, somente um ensaio clínico randomizado com número reduzido de gestantes mostrou efetividade e desfechos semelhantes aos da insulina (30). Uma potencial restrição ao uso da acarbose poderia ser o risco de aumento de parto pré-termo em decorrência da redução da absorção de carboidratos intestinais, que aumentaria a lise bacteriana e as concentrações de butirato, com consequente aumento na secreção de prostaglandina E e aumento prematuro da atividade uterina (26).…”
Section: Acarboseunclassified